EFFECT OF ENRICHED MUNICIPAL SOLID WASTE AMENDED WITH NPK FERTILIZER ON THE GROWTH AND YIELD OF MAIZE - Olalekan, IBIRONKE Henry (Food, Agriculture and Natural Resources - NETWORKS, 2025)
The growth of maize is often influenced by soil fertility, and municipal solid waste (MSW) has the potential to enhance soil quality when appropriately processed and supplemented with necessary nutrients, MSW can function as a beneficial fertilizer, supporting plant growth and improving soil health. This study investigates the effect of different Nitrogen, Phosphorus, and Potassium (NPK) fertilizer rates combined with MSW on the growth and yield of maize. A pot experiment was conducted at the Teaching and Research Farm, Ekiti State University, using a completely randomized design with three replicates. The treatments consisted of 25% NPK+MSW, 50% NPK+MSW, 75% NPK+MSW, 100% NPK+MSW, and a control. Fifty kilograms of MSW were weighed into 15 different pots, with various levels of NPK 15:15:15 (25%, 50%, 75% and 100%) incorporated. Growth metrics such as plant height, leaf area, number of leaves per plant ear height, and stem girth were accessed and yield parameters such as, Length of cob, Diameter of cob, Number of grains per cob, 100 grain weight, and Yield (g/pot) were also measured. The results revealed that the combination of 100% NPK with MSW resulted in significantly higher values for all growth and yield parameters compared to the control. This suggests that the use of MSW in combination with NPK fertilizer, especially at the 100% rate, can significantly enhance maize growth and lead to improved yield, while also contributing to waste management.